Biochemical studies of gastrointestinal cestode parasites in Capra hircus (L.) and Ovis bharal (L.) from Marathwada region - Humbe, Atul; Jadhav, Swati; Borde, Sunita N (International Multidisciplinary Research Journal, 2011)
Parasitic biochemistry has great practical importances through chemotherapy and vaccine production and in understanding of the complex association involved in the host parasite relationship However; information in parasite biochemistry is patchy. It is a field growing in parallel with the new surge of interest in tropical diseases. Where as previously parasitologists have been required to adopt biochemical methodology in order to stay abreast of development. Gastrointestinal cestodes are the most pathogenic parasites in Capra hircus and Ovis bharal in tropic and subtropic areas. Present investigation deals with the biochemistry (Protein, glycogen and lipid) of Cestode parasites in Capra hircus and Ovis bharal.